2005
DOI: 10.1111/j.1747-0765.2005.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of K, Na and Cl in Root and Leaf Cells of Soybean and Cucumber Plants Grown under Salinity Conditions

Abstract: The element contents in the compartments of root and leaf cells of soybean and cucumber plants grown for 8 d in a nutrient solution containing 50 mM NaCl, 25 mM CaCl2 or 50 mM NaCl+4.75 mM CaSO4 were examined by X‐ray microanalysis of freeze‐substituted dry sections. Sodium accumulated in the vacuoles rather than in the cytoplasm and apoplastic space in the root cells of the soybean plants, leading to the difficulty in the transport of Na to leaves in soybean. Salt injury of soybean is considered to be caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Therefore, the salinity tolerance in these soybean cultivars was associated with tolerance to both Na and Cl, although several previous studies had suggested that salt-induced inhibition of growth was more closely associated with Cl than Na contents in aboveground plant parts (Abel and Mackenzie, 1964;Abel, 1969;Parker et al,1983;Yang and Blanchar, 1993;Valencia et al, 2008;Ren et al, 2012). In this respect, Dabuxilatu and Ikeda (2005) ascribed the greater toxicity of Cl to its allocation within the plant: Cl was stored in both vacuoles and apoplastic spaces in both leaves and roots, whereas Na was predominantly stored in vacuoles in roots. In the present study, the saline conditions stimulated the accumulation of Cl more substantially than Na, particularly in shoots (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the salinity tolerance in these soybean cultivars was associated with tolerance to both Na and Cl, although several previous studies had suggested that salt-induced inhibition of growth was more closely associated with Cl than Na contents in aboveground plant parts (Abel and Mackenzie, 1964;Abel, 1969;Parker et al,1983;Yang and Blanchar, 1993;Valencia et al, 2008;Ren et al, 2012). In this respect, Dabuxilatu and Ikeda (2005) ascribed the greater toxicity of Cl to its allocation within the plant: Cl was stored in both vacuoles and apoplastic spaces in both leaves and roots, whereas Na was predominantly stored in vacuoles in roots. In the present study, the saline conditions stimulated the accumulation of Cl more substantially than Na, particularly in shoots (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Supplemental Ca is known to mitigate the adverse effects of salinity on plant growth (Dabuxilatu and Ikeda, 2005). Improvement of plant performance under saline condition using calcium supplement appears greatly to be depend on genetic ability of plant species.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, inhibition of Na entry into roots via regulation of non-selective cation channels (Zhu, 2003) may decline sodium delivery to the plant tissues. Although, supplemental Ca, at least for some plants and conditions, may be a proper approach to moderate the deleterious impacts of salinity (Kent and Läuchli, 1985;Dabuxilatu and Ikeda, 2005). Calciumindependent component of the Na inhibition would negatively influence plant growth responses (Reid and Smith, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benes et al (1996a, b) found that Cl ¡ leaf concentration of 80 mM caused growth inhibition in maize plants at harvest time. Therefore, Cl ¡ leaf concentration should not be the main cause of leaf yellowing, but diVerent subcellular Cl ¡ redistribution could be taking place (Fricke et al 1996;Dabuxilatu and Ikeda 2005), that is, more Cl ¡ accumulation in the vacuole of inoculated plants. Also, noninoculated plants suVered from a water deWcit whereas inoculated plants kept their RWC values similar to nonstressed plants.…”
Section: Bacillus Megaterium Induced Diverent Salt Responsementioning
confidence: 99%